PowerShell for Office 365 : automate Office 365 administrative tasks - Machado, Martín; Bhoyar, Prashant G. (Packt Publishing, 2017)
Learn the art of leveraging PowerShell to automate Office 365 repetitive tasks About This Book Master the fundamentals of PowerShell to automate Office 365 tasks. Easily administer scenarios such as user management, reporting, cloud services, and many more. A fast-paced guide that leverages PowerShell commands to increase your productivity. Who This Book Is For The book is aimed at sys admins who are administering office 365 tasks and looking forward to automate the manual tasks. They have no knowledge about PowerShell however basic understanding of PowerShell would be advantageous. What You Will Learn Understand the benefits of scripting and automation and get started using Powershell with Office 365 Explore various PowerShell packages and permissions required to manage Office 365 through PowerShell Create, manage, and remove Office 365 accounts and licenses using PowerShell and the Azure AD Learn about using powershell on other platforms and how to use Office 365 APIs through remoting Work with Exchange Online and SharePoint Online using PowerShell Automate your tasks and build easy-to-read reports using PowerShell In Detail While most common administrative tasks are available via the Office 365 admin center, many IT professionals are unaware of the real power that is available to them below the surface. This book aims to educate readers on how learning PowerShell for Office 365 can simplify repetitive and complex administrative tasks, and enable greater control than is available on the surface. The book starts by teaching readers how to access Office 365 through PowerShell and then explains the PowerShell fundamentals required for automating Office 365 tasks. You will then walk through common administrative cmdlets to manage accounts, licensing, and other scenarios such as automating the importing of multiple users, assigning licenses in Office 365, distribution groups, passwords, and so on. Using practical examples, you will learn to enhance your current functionality by working with Exchange Online, and SharePoint Online using PowerShell. Finally, the book will help you effectively manage complex and repetitive tasks (such as license and account management) and build productive reports. By the end of the book, you will have automated major repetitive tasks in Office 365 using PowerShell. Style and approach This step by step guide focuses on teaching the fundamentals of working with PowerShell for Office 365. It covers practical usage examp ...